Comparative analysis of Python and Rust: evaluating their combined impact on performance - Przemysław Mroczek; Jakub Mańturz; Marek Miłosz (Journal of Computer Sciences Institute, 2025)
This article presents results of exploration of the combined application of Python and Rust in enhancing software performance, focusing on algorithm implementation. Python, known for its simplicity and flexibility, is widely used in various domains but faces limitations in CPU-intensive tasks. Rust, on the other hand, excels in performance and safety of memory management, making it a compelling choice for optimizing critical code sections. By leveraging tools such as PyO3 and Maturin, Authors examine how Rust's compiled code can be seamlessly integrated into Python projects to mitigate performance bottlenecks.